(untitled) (Journal of Medical & Health Sciences Review, 2025)
Cervicogenic headache (CGH) is a secondary headache resulting from cervical musculoskeletal dysfunction, involving muscles, joints, and nerves. Proper management is directed toward the restoration of cervical mobility, muscle tension reduction, and suppression of nerve irritation. The research compared the impacts of neck mobilization and neck isometric exercises in alleviating CGH symptoms. A randomized controlled trial was undertaken at Isra University, Islamabad Campus, and Social Security Hospital, Rawalpindi, involving 40 patients with CGH, randomly allocated into two groups of 20 each. A group received neck mobilizations, and the other did neck isometric exercises. Findings indicated that both interventions yielded notable improvements within groups. Headache Impact Test (HIT) identified significant decrease in headache intensity over time (p<0.005). Between-group comparison revealed no overall significant difference, however mobilization evidenced superior outcomes. For the Neck Pain and Disability Index (NPDI), both groups manifested notable within-group improvement (p<0.005). Between-group comparison identified no significant difference, but mobilization exhibited superior outcomes at baseline (p=0.019) and at the fourth week (p=0.017). The research concluded that both isometric exercise and neck mobilization are efficacious in treating CGH, with no general superiority of either procedure over the other. Mobilization was mildly superior at subsequent follow-ups, indicating it might offer faster or greater functional recovery in certain patients.